First evidence of east–west migration across the North Pacific in a marine bird. (October 2015) - Gaston, Anthony J.; Hashimoto, Yuriko; Wilson, Laurie; Daunt, Francis
<x xml:space="preserve">Abstract</x> Many marine birds undertake long migrations between breeding and wintering areas, including some species that undertake long‐distance east–west or west–east movements across many degrees of longitude. To date, however, no east–west migrations have been described across the North Pacific. Geolocators were deployed on Ancient Murrelets Synthliboramphus antiquus breeding in Haida Gwaii, British Columbia, in 2013 and four were retrieved the following year. Longitude positions showed that all four moved rapidly westwards after breeding, three of them reaching waters between Japan and China by November and this location was also supported by ringing data. Return migration was rapid, beginning in February and reaching Haida Gwaii in March, providing the first evidence for bird migration spanning the entire width of the North Pacific. This is the longest migration recorded in any of the Alcidae.